Estudos sobre misturas de agregados reciclados de resíduos da construção civil com solos para utilização em pavimentos - Santana, Fagner Ismael Teixeira de (2014)
The growth of the construction industry in Brazil has resulted in increasing of construction and demolition wastes generation (CDW). Given this fact, various studies and researches have been conducted in order to mitigate or even extinguish the undesirable impacts caused by improper disposal of these wastes on the environment. On the other hand, the road infrastructure constructions, in general, consume large amounts of natural resources, that have become scarce in many regions of the country. But fortunately, it is worth noting that this construction area has a favorable history about incorporation of wastes in your construction process, and CDW is the most prominent. Against this background, with this research sought to evaluate the geotechnical properties of CDW recycled aggregates produced by a recycling plant in the Aracaju metropolitan region (AMR), preparing mixtures of these materials with two typically soils of Sergipe state. Therefore, tests were conducted to evaluate the composition and percentage of impurities, gradation, Atterberg limits, absorption, abrasion resistance, bulk density, grain form, compaction, degradation, califórnia bearing ratio and resiliente modulus. Based on results, obtained using the intermediate compaction energy, it was found that the CDW recycled aggregates provided significant improvements in the soils properties, expressed by satisfactory mechanical performance observed in the CBR and RM parameters of mixtures. The results presented in this research indicate and ratify the technical feasibility of using the CDW in base and sub-base pavements layers, which can contribute to sustainable development, increasing the materials supply and a application methodology in AMR and Sergipe urban roads constructions, in addition to resulting in decreased extraction of natural materials and areas of final disposal of such wastes.